Hepatitis B Virus Nucleocapsid but Not Free Core Antigen Controls Viral Clearance in Mice - Lin, Yi-Jiun (American Society for Microbiology, 2012)
We have recently shown that hepatitis B virus (HBV) core antigen (HBcAg) is the major viral factor for HBV clearance using a hydrodynamics-based mouse model. Knockout of HBcAg hampers the development of antiviral immune responses and thus promotes HBV persistence. Here, we further demonstrated that only in the capsid form, but not the free or dimer form, can HBcAg exert its contributory role in HBV clearance. HBcAg is the main structural protein of HBV icosahedral nucleocapsid. A mutant HBV DNA which expresses an assembly-defective HBcAg, HBcAgY132A, surprisingly prolonged HBV surface antigenemia in both C57BL/6 and BALB/c mice without affecting viral transcription and translation. This result was not due to a loss of the possible immune epitope caused by the single-amino-acid substitution of HBcAg. Moreover, the particular HBV mutant failed to induce robust humoral and cellular immunity against HBV. These data revealed the requirement of capsid structure for inducing adequate immunity that leads to HBV clearance in mice.